A phylogenetic and morphological study of the genus Dermoloma (Agaricales, Tricholomataceae) in Europe and North America exposes inefficiency of opportunistic species descriptions - Katarína Adamčíková; Munazza Kiran; Miroslav Caboň; Brandon P. Matheny; Marisol Sánchez-García; Eef Arnolds; Michaela Caboňová; Gilles Corriol; Bálint Dima; Gernot Friebes; Gareth W. Griffith; Django Grootmyers; et al. (IMA Fungus, 2025)
Dermoloma is traditionally known as a small genus of agarics classified in the family Tricholomataceae. This study implemented a multilocus phylogeny of six DNA regions to recognize phylogenetic species within the genus. The species concept is reinforced by observations of well-defined morphological characters enhanced by long term sampling effort in Europe and North America. Thirty European Dermoloma species are described, including 16 new species from Europe and three from North American. These species are classified into two subgenera morphologically distinguished by spores with positive or negative amyloid reaction. A new genus Neodermoloma is introduced for the Dermoloma-like species N. campestre. Localized or continental-scale species endemicity was confirmed based on studied material, but more inclusive phylogenetic clustering supported a mixture of North American species among the European clades. Of the 22 names validly published from Europe prior to this study, 11 could be assigned to well-defined Dermoloma species recognized here. Of the remaining 11 names, two were considered representing Dermoloma species not recorded since their description, and nine were established as later synonyms of other species. Morphological studies of Dermoloma are challenging due to the relatively low number of characters suitable for identification of species. The majority of morphological characters showed continuous variation with high overlap throughout the genus. For this reason, species identification requires an awareness of morphological variability within species, and multiple distinguishing characters need to be combined, and furthermore, often a barcode sequence is needed for a certain identification. Stable isotope analysis in Dermoloma of δ13C and δ15N revealed an ecological signature similar to known CHEGD fungi, i.e. Clavariaceae and Hygrocybe s.l. This indicates that Dermoloma species are biotrophic but neither ectomycorrhizal nor saprotrophic and may form mutualistic root endophytic associations with vascular plants.